TRANSLATION OF GASTRONOMIC TERMINOLOGY IN ANCIENT TIMES (KONFERENSIYA, 2025)
This article provides a comprehensive examination of the translation of gastronomic terminology in ancient civilizations, emphasizing the linguistic, cultural, and historical mechanisms that shaped the transmission of food-related knowledge across languages. In antiquity, gastronomy was not merely a matter of sustenance but a domain deeply intertwined with ritual practices, social structures, economic exchanges, and symbolic meaning. Translators of early Greek, Roman, Mesopotamian, Egyptian, and Chinese texts encountered substantial challenges when attempting to render foreign culinary terms accurately, as many food items, preparation methods, and culinary customs lacked direct equivalents in the target cultures. By analyzing primary sources and modern scholarship, this study highlights the strategies employed by ancient translators—such as borrowing, descriptive paraphrasing, cultural substitution, and semantic expansion—and explores how these strategies influenced cross-cultural understanding of food. Ultimately, this research demonstrates that the translation of gastronomic terminology served as an essential conduit for intercultural communication, facilitating the exchange of culinary practices, ingredients, and broader cultural values